2019
DOI: 10.3390/ma12182994
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Properties of Nano-Hydroxyapatite Reinforced WE43 Alloy Fabricated by Friction Stir Processing

Abstract: This research mainly focuses on the successful fabrication of nano-hydroxyapatite (nHA) reinforced WE43 alloy by two-pass friction stir processing (FSP). Microstructure evolution, mechanical properties, and in vitro corrosion behavior of FSPed WE43/nHA composite and FSPed WE43 alloy were studied. The results show that nHA particles are effectively dispersed in the processing zone, and the well-dispersed nHA particles can enhance the grain refine effect of FSP. The average grain sizes of FSPed WE43 alloy and WE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Jiang et al [42] showed that the degradation rate of extruded WE43, measured in SBF over two days, was ~3.9 mm/year. A similar magnitude of the degradation rate was reported for cast WE43 alloy coated with nano-hydroxyapatite (nHA) particles [43].…”
Section: Resultssupporting
confidence: 73%
“…Jiang et al [42] showed that the degradation rate of extruded WE43, measured in SBF over two days, was ~3.9 mm/year. A similar magnitude of the degradation rate was reported for cast WE43 alloy coated with nano-hydroxyapatite (nHA) particles [43].…”
Section: Resultssupporting
confidence: 73%
“…The corrosion characteristics were measured using Tafel exploration method, as presented in previous studies following ASTM-G31-72 rule. [44][45][46][47][48][49][50] In order to check the degradation rate, the samples were dipped in NaCl solution for 24, 48, and 72 h, respectively. Upon predetermining the time period, samples have been taken out of the solution and were weighed.…”
Section: Corrosion Resistancementioning
confidence: 99%
“…The main focus of this Special Issue is to therefore collect scientific contributions dealing with the development of absorbable metals with improved and unique corrosion and mechanical properties for applications in highly loaded implants, or cardiovascular and urethral stents. This Special Issue assembles a group of highly original manuscripts that present a range of exciting innovations in alloying [ 1 , 2 , 3 ] and compositing [ 4 ], along with their testing and assessments [ 5 , 6 , 7 ] to introduce novel medical implants based on magnesium [ 2 , 3 , 4 , 8 , 9 ], zinc [ 1 , 7 ], or iron [ 10 , 11 ]. As the biointerface plays an important role in implant–tissue interactions, contributions to implant coating and surface engineering strategies and their effects on the implant properties and corrosion are also discussed [ 8 , 10 , 12 ].…”
mentioning
confidence: 99%